2016
DOI: 10.3171/2015.5.jns141901
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor effect with indoleamine 2,3-dioxygenase inhibition and temozolomide in a murine glioma model

Abstract: M alignant glioma is the most common brain tumor in adults; it has an aggressive lethal nature and a median survival of only 14 months, despite the standard established therapy of maximum resection followed by radiation and chemotherapy. Several immunotherapies, such as dendritic cell therapy, have been evaluated as new adjuvant approaches. However, the efficacy of immunotherapy for patients with malignant glioma is limited for several reasons, including the anatomical isolation of the central nervous system b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 33 publications
0
62
0
1
Order By: Relevance
“…Studies were excluded because of following reasons: (1) not sufficient survival data reported, (2) letters, reviews, commentary, perspectives, case reports, conference abstracts, editorials or expert opinion, (3) studies reporting xenograft results in immunodeficient or humanized mice. Overall these search criteria helped short-list 15 research articles 12,15,16,[50][51][52][53][54][55][56][57][58][59][60][61] mentioned in Box S1.…”
Section: Methodsmentioning
confidence: 99%
“…Studies were excluded because of following reasons: (1) not sufficient survival data reported, (2) letters, reviews, commentary, perspectives, case reports, conference abstracts, editorials or expert opinion, (3) studies reporting xenograft results in immunodeficient or humanized mice. Overall these search criteria helped short-list 15 research articles 12,15,16,[50][51][52][53][54][55][56][57][58][59][60][61] mentioned in Box S1.…”
Section: Methodsmentioning
confidence: 99%
“…Hanihara et al reported 1MT significantly suppressed tumor growth in a murine glioma model. 1MT also had synergistic effects with temozolomide (193). Li et al showed that mice bearing intracranial GL 261 glioblastoma tumors that were treated with 1MT added to radiation therapy plus temozolomide and cytoxan, survived longer than mice treated with chemotherapy and radiation therapy alone (194).…”
Section: Inhibitors Of the Kynurenine Pathwaymentioning
confidence: 99%
“…Indoleamine 2,3-dioxygenase (IDO) is another checkpoint molecule expressed by glioblastoma to suppress immune function [18]. Preclinical models showed that strategies involving IDO inhibition were active [19,20], in fact, Phase I clinical trials with indoximod, an IDO inhibitor started (NCT02052648).…”
Section: Combination Therapiesmentioning
confidence: 99%